2009
DOI: 10.1242/jcs.054791
|View full text |Cite
|
Sign up to set email alerts
|

The growth-promoting effect of KGF on limbal epithelial cells is mediated by upregulation of ΔNp63α through the p38 pathway

Abstract: Corneal epithelial stem cells are thought to reside in the limbus, the transition zoon between cornea and conjunctiva. Keratinocyte growth factor (KGF) and hepatocyte growth factor (HGF) are two paracrine factors that regulate the proliferation, migration and differentiation of the limbal epithelial cells; however, the underlying mechanisms are still poorly understood. In an ex vivo limbal explant culture, we found that KGF is a more potent growth stimulator for the epithelial outgrowth than HGF. Immunofluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 50 publications
2
44
0
Order By: Relevance
“…Previous studies have demonstrated that IGF-I and IGF-II can support the proliferation of keratinocytes [13] and, together with substance P, promote the growth of rabbit corneal epithelial cells [33,34]. A similar growth-promoting effect of KGF and HGF on limbal epithelial cells in the rabbit was described by Cheng et al [10]. In our mouse model, IGF-I, which induced the differentiation of LSC, did not support the proliferation of limbal cells, even though it was tested over a wide range of concentrations.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Previous studies have demonstrated that IGF-I and IGF-II can support the proliferation of keratinocytes [13] and, together with substance P, promote the growth of rabbit corneal epithelial cells [33,34]. A similar growth-promoting effect of KGF and HGF on limbal epithelial cells in the rabbit was described by Cheng et al [10]. In our mouse model, IGF-I, which induced the differentiation of LSC, did not support the proliferation of limbal cells, even though it was tested over a wide range of concentrations.…”
Section: Discussionsupporting
confidence: 63%
“…Among them, the genes coding for growth and differentiation factors represent a significant group. It was shown that the transforming growth factor-a (TGF-a), TGF-b, epidermal growth factor (EGF), hepatocyte growth factor (HGF), and fibroblast growth factor-b (FGF-b), which are produced by corneal epithelial cells, can modulate the proliferation and growth of cells on the ocular surface [10][11][12]. Another factor produced by the corneal epithelium, insulin-like growth factor-I (IGF-I), has been shown to support the proliferation of keratinocytes [13], enhance the production of the adherens-junction protein N-cadherin [14], stimulate the formation of the extracellular matrix [15], and increase the synthesis of collagen by keratinocytes [16].…”
Section: Introductionmentioning
confidence: 99%
“…Limbal basal cell layers preferentially express certain structural proteins (vimentin, cytokeratin 14, 15 and 19), cell adhesion molecules (integrin α6, β1, The chemotactic signal for centripetal migration may be provided in the form of cytokines and/or the difference between the composition of extracellular matrix between the limbus and the cornea [59] . KGF, a paracrine hormone secreted by stromal cells, has been shown to enhance outgrowth in rabbit limbal explant culture on human amniotic membrane [60] . While the inflammatory cytokine interleukin-6 [61] , fibronectin [62] , and hyaluronan [63] , all of which are highly up-regulated upon injury, have been shown to play a role in drawing rabbit limbal cells towards the wound.…”
Section: Biochemical Characteristicsmentioning
confidence: 99%
“…The adenovirus vector, designated Ad-DNp63, was constructed as described before. 25 A recombinant adenovirus carrying only GFP was used as a control. Briefly, viral stock was diluted into 0.5 ml culture medium and added to the culture dishes.…”
Section: Infection Of Recombinant Adenovirus Vectorsmentioning
confidence: 99%
“…A range of PCR reaction cycles (25,27,30,33,36,39 and 40 cycles) were performed to evaluate the relative abundance of p63 transcripts. Diluted cDNA (1:4; 12.5 ng/50 ml PCR reaction) undergoing 25 and 30 PCR cycles was observed to be within the logarithmic phase of amplification and yielded reproducible results with the primers used.…”
Section: Semi-quantitative Pcrmentioning
confidence: 99%